Mental health specialist video consultations for patients with somatic symptom disorder in primary care: protocol for a randomised feasibility trial (the VISION trial). Issue 4 (11th April 2022) - Haun, Markus W; Tönnies, Justus; Graue, Leike; Hartmann, Mechthild; Wensing, Michel; Szecsenyi, Joachim; Wild, Beate; Friederich, Hans-Christoph
Abstract : Introduction: General practitioners (GP) report increasing difficulties in referring patients with somatic symptom disorder (SSD) in specialised psychosocial care. Barriers are structural conditions of the respective healthcare system and patients' reservations against receiving specialised psychosocial care. As patients with SSD often predominantly assume somatic influencing factors for the development and maintenance of their somatic complaints, close collaboration between the GP and mental health specialist (MHS) seems particularly important. Integrating internet-based video consultations by remotely located MHS and primary care can improve effective treatment of patients with SSD by overcoming structural barriers and provide low-threshold and timely care. The aim of this randomised controlled feasibility trial is to investigate the feasibility of implementing MHS video consultations in primary care practices. Methods and analysis: Fifty primary care patients with SSD will be individually randomised in two groups receiving either enhanced treatment as usual as provided by their GP (control group) or two versus five video consultations conducted by an MHS additionally to enhanced treatment as usual. The video consultations focus on (a) diagnostic clarification, (b) the development of a biopsychosocial disorder model, and (c) development of a treatment plan against the background of a stepped-care algorithm based on clinical outcomes. We will investigate the following outcomes: effectiveness of the recruitment strategies, patient acceptance of randomisation, practicability of the technical and logistical processes related to implementing video consultations in the practices' workflows, feasibility of the data collection and clinical parameters. Ethics and dissemination: This trial has undergone ethical scrutiny and has been approved by the Medical Faculty of the University of Heidelberg Ethics Committee (S-620/2021). The findings will be disseminated to the research community through presentations at conferences and publications in scientific journals. This feasibility trial will prepare the ground for a large-scale, fully powered randomised controlled trial. Trial registration number: DRKS00026075.